Monographie der paläarktischen Coryphiini (Coleoptera, Staphylinidae, Omaliinae). Supplementum 1. - Zerche, Lothar (Contributions to Entomology = Beiträge zur Entomologie, 1993)
One genus and 12 species of the Palaearctic Coryphiini are described as new: Coryphium turcicum sp. n. (NE-Turkey); Coryphium loebli sp. n. (Nepal); Coryphium smetanaorum sp. n. (Nepal); Coryphiodes franzi sp. n. (Kashmir); Coryphiodes schuelkei sp. n. (Tadzhikistan); Altaioniphetodes gen. n., type species Altaioniphetodes ryvkini sp. n. (Altai); Ophthalmoniphetodes piger sp. n. (Rila Mountains); Ophthalmoniphetodes maljovicensis sp. n. (Rila Mountains); Eudectus reductus sp. n. (Wrangel Island); Boreaphilus schawalleri sp. n. (Khabarovsk); Boreaphilus hokkaidensis sp. n. (Hokkaido, Sachalin), and Boreaphilus wunderlei sp. n. (Cordillera Cantabrica). The new taxa are integrated in the phylogenetic system of the tribe. All new species are figured. Zoogeographical features are discussed and records mapped. Additional records of known species are noted. Some relations between the Palaearctic and Nearctic partial faunas are discussed and their diversities compared. Keys are partly made new to add the new taxa. The system of the tribe Coryphiini by Watanabe (1990) is discussed and corrected. Nomenclatural Actsryvkini Zerche, 1993 (Altaioniphetodes), spec. n.hokkaidensis Zerche, 1993 (Boreaphilus), spec. n.schawalleri Zerche, 1993 (Boreaphilus), spec. n.wunderlei Zerche, 1993 (Boreaphilus), spec. n.franzi Zerche, 1993 (Coryphiodes), spec. n.schuelkei Zerche, 1993 (Coryphiodes), spec. n.loebli Zerche, 1993 (Coryphium), spec. n.smetanaorum Zerche, 1993 (Coryphium), spec. n.turcicum Zerche, 1993 (Coryphium), spec. n.reductus Zerche, 1993 (Eudectus), spec. n.maljovicensis Zerche, 1993 (Ophthalmoniphetodes), spec. n.piger Zerche, 1993 (Ophthalmoniphetodes), spec. n.Altaioniphetodes Zerche, 1993 (Staphylinidae), gen. n.